(untitled) (Latakia University (formerly Tishreen)Journal for Research and Scientific Studies - Economic and Legal Sciences Series, 2026)
The research aimed to study the impact of asset management on firm value by applying it to the 51 Manufacturing companies listed in the markets of muscat and Jordan, during the period from 2016-2024. The required data were obtained from the annual reports published in the financial statements of the companies under study. Data were analyzed using E-Views10. The research dealt with the firm value as a dependent variable and it was measured by the Tobin’s Q, while the Assets Management was measured by total assets turnover ratio, total fixed assets turnover ratio, and working capital turnover ratio as an independent variable. The results showed that there is a positive effect of asset management measured by total asset turnover rate and fixed asset turnover rate on the value of the company, and there was no effect of asset management measured by working capital turnover on the value of the company in the Muscat market. While The results showed that there was no effect of asset management measured by fixed asset turnover rate and working capital turnover on the value of the company, and there was a positive effect of asset management measured by total asset turnover rate on the value of the company in the Jordan market.